2013
DOI: 10.5146/tjpath.2013.01186
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of maturation status of tumor-infiltrating dendritic cells in invasive ductal carcinoma of the breast: relation with vascular endothelial growth factor expression

Abstract: Mature dendritic cell count correlates with good prognostic features in invasive ductal carcinoma of the breast, suggesting their role in initiating primary anti-tumor immune response. Vascular endothelial growth factor expression may play a role in inhibition of dendritic cell maturation sequence in the tumor microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…Thus, the increased osmotic fragility of mDCs is more sensitive, and the decreased hypo-osmolality resistance of mDCs induced by VEGF cytokine may lead to their cytolysis in TME. This might be one of the reasons for less infiltration of mDCs in tumor tissue and draining lymph nodes and/or for a decline of local immune response in tumors [46,47]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the increased osmotic fragility of mDCs is more sensitive, and the decreased hypo-osmolality resistance of mDCs induced by VEGF cytokine may lead to their cytolysis in TME. This might be one of the reasons for less infiltration of mDCs in tumor tissue and draining lymph nodes and/or for a decline of local immune response in tumors [46,47]. …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the contact area between mDCs and naive T cells would became smaller as the reduced deformability, which might impair the formation of immune synapses and eventually reduce the activation efficiency of T cells in lymph node. VEGF expression is correlated directly with positive nodal metastases and correlated inversely with the count of mDCs [47], and thus, there are different degrees of influence on mDCs in various tumor patients.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, high abundance (above the median) of resting DCs is associated with worse prognosis [ 26 ]. Several molecules expressed or secreted by BC cells, such as polyamines [ 23 ], growth factors [ 27 , 28 ], interleukins and cytokines [ 28 , 29 ], were found to affect DCs properties.…”
Section: Discussionmentioning
confidence: 99%
“…Lopez et al observed high densities of these and DC-LAMP + cell populations in high-grade triple-negative BC [ 32 ]. In contrast, other authors suggested that there are associations between more mature DCs and low-grade IBC [ 27 ] or no relationship between CD1a + DCs and IBC grade [ 27 , 31 ]. Therefore, it appears that the distribution of DCs subsets in tumors of different grades remains similar during the transition from DCIS to IBC.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that incubation of tumor-associated DCs with VEGF and oncostatin M can direct progenitor cell differentiation away from the DC pathway to an ELC fate ( 11 ). Furthermore, the tumor microenvironment can induce the ELD of iDCs, but not of mature DCs ( 22 24 ). While these previous studies have examined the effect of DC differentiation stage on the transition to ELCs, to the best of our knowledge, there is no previous study that addresses whether the degree of differentiation of tumor cells can influence the ELD of iDCs.…”
Section: Discussionmentioning
confidence: 99%